Synthesis and Bioactivity of Novel Sulfonate Scaffold-Containing Pyrazolecarbamide Derivatives as Antifungal and Antiviral Agents - Lei, Zhi-Wei; Yao, Jianmei; Liu, Huifang; Ma, Chiyu; Yang, Wen (Frontiers in Chemistry, 2022)
Novel pyrazolecarbamide derivatives bearing a sulfonate fragment were synthesized to identify potential antifungal and antiviral agents. All the structures of the key intermediates and target compounds were confirmed by nuclear magnetic resonance (NMR) and high-resolution mass spectrometry (HRMS). The single-crystal X-ray diffraction of the compound T22 showed that pyrazole carbamide is a sulfonate. The in vitro antifungal activities of the target compounds against Colletotrichum camelliae, Pestalotiopsis theae, Gibberella zeae, and Rhizoctonia solani were evaluated at 50 µg/mL. Among the four pathogens, the target compounds exhibited the highest antifungal activity against Rhizoctonia solani. The compound T24 (EC50=0.45 mg/L) had higher antifungal activity than the commercial fungicide hymexazol (EC50 =10.49 mg/L) against R. solani, almost similar to bixafen (EC50 =0.25 mg/L). Additionally, the target compounds exhibited protective effects in vivo against TMV. Thus, this study reveals that pyrazolecarbamide derivatives bearing a sulfonate fragment exhibit potential antifungal and antiviral activities.